(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This Paper Present to study of the Physico-chemical Parameters of Ground water of the prime source of fresh water in Maihar Tehsil of Satna district. The water samples are collected from the eleven sites selecting at least one from each ward of that area, first sampling is done in the month of November 2018 and the other in February 2019. The physico -chemical parameters viz., colour, odor, water temperature, transparency , turbidity, electrical conductivity (EC), total dissolved solid (TDS), hardness, alkalinity, chloride, calcium, pH and biochemical oxygen demand (BOD) were analyzed. In the most of the samples, water is colorless and does not impart turbidity.TDS was very high in almost all the samples. The water is moderately hard. The concentration of calcium was within acceptable limit. The pH is above neutral in all the samples hence shows alkalinity. Chloride concentration was very high in the collected samples. The values of BOD were reported to be high in the samples collected from the different sampling stations.